Pengaruh Service Recovery Pada Kepuasan Pelanggan : studi Kasus AUTO2000 Bandung - Surbakti, Nurhayati; Widyarini, Maria (Business Administration Study Program - Universitas Katolik Parahyangan, 2010)
The primary objective of this study is to investigate the effects of service recoveryon customer satisfaction. Specifically, it examines the perception of âjusticeâ in ser-vice recovery and how it affects the level of satisfaction and behavioral outcomes.In addition, the study also explores whether the ârecovery paradoxâ exitsts. Datawere collected through a survey using a structured questionnaire. The 152 respon-dents were analyzed according to whether they did or did not make a complaint tothe service providers. The findings showed that the complainantsâ level satisfactionwith service recovery was not significantly yet affected by perceived justice. Thebehavioral outcomes of the complainants in terms of trust, word-of-mouth (WOM)and loyalty were not either found to be affected by their satisfaction with the servicerecovery. T-test indicated that respondents who were initially satisfied with the ser-vice did not expressed greater trust, loyalty, and positive WOM compared with thesatisfied complainants.Keywords: customer satisfaction, service recovery, and complaint